1989
DOI: 10.1080/02566702.1989.9648175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensity and frequency of defoliation on aerial growth and carbohydrate reserve levels inAcacia karrooplants

Abstract: Acacia karroo trees were defoliated by goats at two intensities and four frequencies; 2, 4, 8 and 12-weekly. Leaf accumulation and carbohydrate reserve levels were compared to a non-defoliated control, and to plants (defoliation controls) which were defoliated for the first time that season each time a frequency treatment was defoliated. These plants are activated by defoliation in such a manner that successive defoliations can result in this activation being additive. There is clearly a defoliation level belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…1), similar to that following natural browsing (e.g. Pellew 1984;Teague 1989a). However, leaf biomass in new shoots of pruned plants did not increase significantly and the proportion of the foliage in new shoots was slightly reduced when compared with unpruned trees (Table 1).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…1), similar to that following natural browsing (e.g. Pellew 1984;Teague 1989a). However, leaf biomass in new shoots of pruned plants did not increase significantly and the proportion of the foliage in new shoots was slightly reduced when compared with unpruned trees (Table 1).…”
Section: Discussionmentioning
confidence: 79%
“…In this study, a test was made of whether the plants compensate for pruning by producing more biomass of new shoots (Teague 1989a;du Toit et al 1990) and leaves of enhanced nutritional quality (du Toit et al 1990), and whether pruning leads to an increase in the plant's physical defences against browsing (Milewski et al 1991). A further test was to see whether there is a relation between resource allocation and growth, chemical and physical defence, and the concentrations of nitrogen in leaves following pruning, as this relation is crucial to understand the outcome of the response of the plant.…”
Section: Functional Ecology 1997 11 106-111 Induced Plant Responses mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that modification to the hormonal balance within the plant following defoliation can result in compensatory growth through stimulated growth and photosynthate production and the reallocation of reserves from elsewhere in the plant (McNaughton 1979). In woody plants, carbohydrate reserves are, generally, reduced following defoliation, especially after severe defoliation, and subsequent regrowth tends to be positively correlated with the carbohydrate status of the plant (see Teague 1989). In Acacia karroo plants, lowest levels of regrowth were observed in the early-flush phenophase when carbohydrate reserves were at their lowest but as the growing season progressed, reserves accumulated and defoliation resulted in higher production (Teague 1989).…”
Section: Introductionmentioning
confidence: 98%